2016
DOI: 10.15253/2175-6783.2016000300013
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and metabolic profile and its relationship with insulin resistance among school children

Abstract: Objective: to investigate the clinical and metabolic profile and its relationship with insulin resistance among school children. Methods: a cross-sectional study of 186 adolescents aged 10 to 19 years old. Clinical variables were: body mass index, waist circumference, and neck, conicity index, systolic, diastolic and mean blood pressure; and metabolic variables were: triglycerides, glucose, total cholesterol, high-density lipoprotein and low-density lipoprotein cholesterol, insulin and Homeostasis Model Assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
1
1
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
1
1
1
1
Order By: Relevance
“…It was presented with altered levels in 28% of the research subjects, and it is considered one of the complications of obesity. This result is similar to the data collected in a study carried out with 186 adolescents aged 10 to 19 years old, which observed IR predominance in 42.5% of research participants; (5) and to the research carried out with 121 obese children and adolescents, aged 6 to 17 years old, in Coimbra, Portugal, which observed the presence of IR in 38.1% of them, using HOMA-IR with 3 as a cutoff point; in that same study, 12.5% of individuals had some form of dyslipidemia. (3) Moreover, higher frequencies were found in a research with 321 obese adolescents aged 10 to 17 years old, with 65% of assessed subjects presenting IR.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…It was presented with altered levels in 28% of the research subjects, and it is considered one of the complications of obesity. This result is similar to the data collected in a study carried out with 186 adolescents aged 10 to 19 years old, which observed IR predominance in 42.5% of research participants; (5) and to the research carried out with 121 obese children and adolescents, aged 6 to 17 years old, in Coimbra, Portugal, which observed the presence of IR in 38.1% of them, using HOMA-IR with 3 as a cutoff point; in that same study, 12.5% of individuals had some form of dyslipidemia. (3) Moreover, higher frequencies were found in a research with 321 obese adolescents aged 10 to 17 years old, with 65% of assessed subjects presenting IR.…”
Section: Discussionsupporting
confidence: 90%
“…(21) Despite its causes being preventable, excessive weight has been growing worse in this age gap, thus becoming the health issue in largest evolution worldwide. (5) Prevalence observed in literature suff ers slight diff erences when compared to the data presented in this study. Th ey vary between minimum values at 11.2% to maximum at 38% of overweight children and adolescents.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…A RI é desencadeadora da síndrome metabólica (SM), estando associada à obesidade, pré-diabetes, diabetes mellitus tipo 2 e vários outros fatores de risco cardiometabólico (Nogueira-de-Almeida & Mello, 2018;Kostovski, et al, 2018;Bielemann, et al, 2015). As taxas de prevalência de RI variam de 5,5% a 72,3% em adolescentes, dependendo do método utilizado (Vikram, 2017;Leal, et al, 2016). Dessa forma, a identificação precoce da RI nesse Research, Society and Development, v. 9, n. 12, e29291210786, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i12.10786 público é relevante sob o ponto de vista da saúde pública (Park, Lee & Lee, 2017).…”
Section: Introductionunclassified